INDICATIONS OF AN INCREASE IN THE INCIDENT OF CAESAREA SECTIO IN THE IHC LAVALETTE HOSPITAL, MALANG CITY - Salsabila, Jauhar Roulfia; Pertami, Sumirah Budi; Supono, Supono; Kasiati, Kasiati (Indonesian Journal of Applied Health, 2024)
Caesarean section confinement method is one of the alternatives for confinement. The purpose of this study was to determine what indications are related to the increasing incidence of caesarean sections at Lavalette Hospital. The type of research used in this study is descriptive research, with a cross-sectional design. The population in this study were all used as samples totaling 69 mothers giving birth. Data collection in this study used primary data by giving questionnaires to patients giving birth. Analysis was carried out using univariate, bivariate and multivariate tests. The results of the study showed that 32 (46.4%) were included in the criteria for performing a caesarean section, there was an indication of a relationship between gestational age, premature rupture of membranes (PROM), preeclampsia, breech position and prolonged labor with cesarean section procedures in mothers giving birth at Lavalette Hospital, Malang. The result of the analysis of sectio caesarea indication showed that caesarean section was the dominant indication for procedures at Lavalette Hospital, Malang, with a p-value of 0.000<0.0005 and the highest Odds Ratio value of 92. This means that mothers who experience have a 92-fold greater chance of undergoing a caesarean section compared to other variables.